Southeast Asia and China a contest in mutual socialization - Dittmer, Lowell; Ngeow, Chow Bing (World Scientific, 2017)
"The recent uncertainties over the South China Sea have become one major issue in the relations between China and Southeast Asian countries. The South China Sea issue, however, is countered by the deepening economic integration between China and Southeast Asia, which is likely to continue should China's proposal for a 21st Century Maritime Silk Road is agreed and implemented. Yet the success or not of this proposal depends also on the interactions in the political-security sphere between both sides. Southeast Asia and China: Exercises in Mutual Socialization brings together experts from different disciplines to illuminate on the complex political, economic and normative interactions between China and the Southeast Asian countries. This book analyses key issues including the national identity discourse of China as a Great Power, China's civil-military interactions in its strategy in the South China Sea dispute, the different kinds of political and strategic strategies used by Southeast Asian countries in countering China, the past patterns and present trajectories of economic ties between China and Southeast Asian countries, as well as the strategic implications of China's 21st Century Maritime Silk Road initiative".